2017
DOI: 10.1177/2378023117741724
|View full text |Cite
|
Sign up to set email alerts
|

Do Asian Americans Face Labor Market Discrimination? Accounting for the Cost of Living among Native-born Men and Women

Abstract: Being nonwhite, Asian Americans are an important case in understanding racial/ethnic inequality. Prior research has focused on native-born workers to reduce unobserved heterogeneity associated with immigrants. Native-born Asian American adults are concentrated, however, in areas with a high cost of living where wages tend to be higher. Regional location is thus said to inflate the wages of Asians. Given that many labor markets are national in scope with regional migration being common, current place of residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Foreign educational credentials may be lower quality than U.S. credentials (or perceived as such) (Zeng and Xie 2004) or less transferrable in the U.S. context (Bratsberg and Ragan 2002); further, foreign-educated Asian-origin workers may have poor English language ability (Espenshade and Fu 1997) or relatively limited social networks (Sakamoto et al 2009). The Heterogeneity approach also allows for foreign-educated Asian-origin individuals to be penalized for personality-related reasons, either because those differences truly exist due to the difficulty of acculturation (Wang et al 2017) or because employers use stereotypes specific to Asian immigrants when evaluating foreign-educated Asian-origin workers (Oreopoulos 2011). Whether based in truth or not, there is evidence that perceptions of personality differ by Asian immigrant generation.…”
Section: The Theoretical Asian Personality Penalty At the Point Of Hirementioning
confidence: 99%
See 2 more Smart Citations
“…Foreign educational credentials may be lower quality than U.S. credentials (or perceived as such) (Zeng and Xie 2004) or less transferrable in the U.S. context (Bratsberg and Ragan 2002); further, foreign-educated Asian-origin workers may have poor English language ability (Espenshade and Fu 1997) or relatively limited social networks (Sakamoto et al 2009). The Heterogeneity approach also allows for foreign-educated Asian-origin individuals to be penalized for personality-related reasons, either because those differences truly exist due to the difficulty of acculturation (Wang et al 2017) or because employers use stereotypes specific to Asian immigrants when evaluating foreign-educated Asian-origin workers (Oreopoulos 2011). Whether based in truth or not, there is evidence that perceptions of personality differ by Asian immigrant generation.…”
Section: The Theoretical Asian Personality Penalty At the Point Of Hirementioning
confidence: 99%
“… 4. Later studies confirmed Kim and Sakamoto’s (2010) suspicion that the wage penalty they found for U.S.-born Asian men was due to overcontrolling for geographic region, as U.S.-born Asian men choose to live on the west coast where wages are higher (e.g., Wang et al 2017). …”
mentioning
confidence: 91%
See 1 more Smart Citation
“…A bachelor’s degree in many STEM fields actually yields higher lifetime earnings than a graduate degree in many non-STEM areas (Kim et al., 2015). As is well-known, Asian Americans are over-represented in prestigious American universities and in higher-paying STEM-related fields of study (Kim and Sakamoto, 2010; Wang et al., 2017; Zhou and Lee, 2017). For this reason, the claims made by Zhou and Lee (2017: 10), Tran et al.…”
Section: Drawing Conclusion About Educational Attainment While Ignormentioning
confidence: 99%
“…Caudill and De Vos, 1956; Jiménez and Horowitz, 2013; Kasinitz et al., 2008; Kitano, 1976; Lee and Zhou, 2015; Petersen, 1966; Schneider and Lee, 1990) . The higher levels of educational attainment along with their chosen fields of study result in higher levels of income and occupational attainment among Asian Americans (Kim and Sakamoto, 2010; Sakamoto and Hsu, 2020; Wang et al., 2017; Xie and Goyette, 2003).…”
Section: Intergenerational Mobility Depends On Family Processes Whichmentioning
confidence: 99%